Using natural intervention to promote subjective well-being of essential workers during public-health crises: A Study during COVID-19 pandemic. (February 2022) - Hu, Chenhao; Zhu, Ke; Huang, Kun; Yu, Bo; Jiang, Wenchen; Peng, Kaiping; Wang, Fei
Abstract: Essential workers such as medical workers and police officers are first-line fighters during public-health crises, such as COVID-19 pandemic. Every time, they are under heavy stress both physically and mentally. The goal of the present study was to develop a novel nature-based intervention to promote their well-being. A representative sample of essential workers in China was recruited for a five-day intervention program, and were randomly assigned to two groups. The experimental group watched 2-min video clips of natural scenes every day, while the control group watched urban scenes. Results indicated that after five days, the natural stimuli intervention yielded overall improvements in various indices of subjective well-being. Furthermore, analyses of nested longitudinal data confirmed that everyday nature stimuli exposure provided both immediate and repeated restorative benefits. The proposed natural-based intervention is brief and easy-to-use, offering a cost-efficient psychological booster to promote subjective well-being of essential workers during this crisis time. Highlights: We developed a novel nature-based intervention for COVID-19 essential workers (medical workers and police officers). The effectiveness of the intervention was tested in a nested longitudinal study. Daily brief exposure to nature yielded instant and repeated restorative effects on essential workers' subjective well-being. The natural environment offers a cost-efficient psychological booster for essential workers during public health crises.